Stable homes, strong families: reimagining housing policies and programs for Indigenous peoples living with and affected by HIV and AIDS in Canada. Issue 2 (4th May 2018) - Ion, Allyson; Greene, Jonathan; Masching, Renée; Poitras, Margaret; Brownlee, Patrick; St. Denys, Raye; Greene, Saara; Jackson, Randy; Worthington, Catherine; Amirault, Marni; Nyman, Sheila; Anaquod, Jaqueline
ABSTRACT: Stable Homes, Strong Families (SHSF) is a community-based research project that sought to investigate the connection between HIV, housing and Indigenous cultures and identify strategies to ensure culturally appropriate housing programs and policies for Indigenous peoples living with and affected by HIV. The impetus for this research stems from a body of knowledge that recognizes the inextricable link between housing and health, as well as growing momentum in Canada to reimagine the relationship between Indigenous and non-Indigenous peoples through decolonizing approaches and reconciliation. This paper outlines a number of solution-focused social policy recommendations that emerged from SHSF research findings to Indigenize the creation and management of housing for Indigenous peoples living with and affected by HIV. Recommendations include creating spaces for ceremonial practices and cultural traditions; integrating processes for community engagement and consultation; breaking down silos that exist between health, housing, and urban development stakeholders; and providing wrap around support services from an Indigenous perspective. In advocating for these recommendations, we aim to stimulate a dialog regarding how, and by whom, housing policies and practices can be developed, implemented, and mandated to best support Indigenous peoples living with and affected by HIV and AIDS across Canada and around the world.